2021
DOI: 10.1212/con.0000000000000993
|View full text |Cite
|
Sign up to set email alerts
|

Headache in Children and Adolescents

Abstract: PURPOSE OF REVIEW: This article reviews the approach to a child or adolescent with headache, the criteria for common diagnoses, and the evidence base for treatments.RECENT FINDINGS: The guidelines for acute and preventive treatment of migraine were updated in 2019. These guidelines summarize the available evidence and outline the questions that should be addressed in future research. The US Food and Drug Administration (FDA) approval of several new classes of drugs and devices to treat adult migraine in the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 127 publications
(305 reference statements)
1
25
0
8
Order By: Relevance
“…Risk of PTH was greater up to three months following mTBI and especially for children without premorbid headache, indicating that headache onset immediately after injury could reflect specific and early effects of pediatric mTBI. This is consistent with the reported role of head trauma as a leading cause of PTH in pediatric emergency departments (24). Still, the mechanisms underlying PTH, as well as the neurobiology of both pediatric mTBI and headache, are complex and poorly understood (6,11,25).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Risk of PTH was greater up to three months following mTBI and especially for children without premorbid headache, indicating that headache onset immediately after injury could reflect specific and early effects of pediatric mTBI. This is consistent with the reported role of head trauma as a leading cause of PTH in pediatric emergency departments (24). Still, the mechanisms underlying PTH, as well as the neurobiology of both pediatric mTBI and headache, are complex and poorly understood (6,11,25).…”
Section: Discussionsupporting
confidence: 92%
“…For example, psychological distress and impoverished sleep are common post-concussive symptoms and leading triggers of pediatric headache (27). Interestingly, they are implicated in migraine as well as TTH (24), both of which occurred in our mTBI group. Consistent with other studies, we found that older children and females demonstrated higher risk of headache and prolonged headache duration (46).…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…In a similar study, Inaloo et al observed a higher ratio of headache (Second Edition of The International Headache Classification, ICHD-2) prevalence in children with functional constipation (Rome III criteria) than in the control group-19.8% vs. 5.6% [137]. However, this relationship was significant only in mild, nonmigraine headache subptypes and the authors concluded that it might result from emotional stress, depression, and anxiety, but these results and their interpretation should be considered with as great care as other results on headache in children [138].…”
Section: Migraine and Functional Gi Disordersmentioning
confidence: 87%
“…Children and adolescent, significant only in nonmigraine subtypes [138] Functional dyspepsia Patients aged 18-55 years, higher migraine prevalence in dysmotility-like dyspepsia as compared with controls, patients with ulcer-like dyspepsia and reflux-like dyspepsia [139] IBS Many studies [143] a -abbreviations: CVS, cyclic vomiting syndrome; GERD, gastroesophageal reflux disease; IBS, irritable bowel syndrome.…”
Section: Cvs Amentioning
confidence: 99%